1983
DOI: 10.1002/chin.198337004
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: HIGH‐FIELD ALUMINUM‐27 NMR STUDIES ON THE ALUMINUM COORDINATION IN CRYSTALLINE ALUMINUM PHOSPHATES

Abstract: Die im Hochfeld bei schneller Probenrotation um den Magischen Winkel verschmälerten "Al‐NMR‐Spektren gestatten eine direkte Koor ‐ dinationszahlbestimmung des Aluminiums.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…Manganese (Mn 2+) replaces aluminium in A1PO4-5 and despite having an unpaired electron, Tle is sufficiently short that only moderate broadening occurs and the contact shift is small [243]. Glasses from the system CaO-A1203-P205 showed three peaks at -21, 4 and 37 ppm which were assigned to AI(OP)6, Al(OAl)6 and AI(OP)4 [244]. Similar spectra were observed from alkali aluminophosphate glasses [245], Sb203-A1203-P205 [246] and the binary A1203-P205 [245] precluding cation effects being their source.…”
Section: Aluminophosphatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Manganese (Mn 2+) replaces aluminium in A1PO4-5 and despite having an unpaired electron, Tle is sufficiently short that only moderate broadening occurs and the contact shift is small [243]. Glasses from the system CaO-A1203-P205 showed three peaks at -21, 4 and 37 ppm which were assigned to AI(OP)6, Al(OAl)6 and AI(OP)4 [244]. Similar spectra were observed from alkali aluminophosphate glasses [245], Sb203-A1203-P205 [246] and the binary A1203-P205 [245] precluding cation effects being their source.…”
Section: Aluminophosphatesmentioning
confidence: 99%
“…Similar spectra were observed from alkali aluminophosphate glasses [245], Sb203-A1203-P205 [246] and the binary A1203-P205 [245] precluding cation effects being their source. Early work was hampered by loss of intensity with some samples showing as little as 20% of the total aluminium content [244].In the antimony system at high antimony contents a fourth resonance at (51-57) ppm became dominant [246]. More recent studies at higher magnetic fields have shown that in xAl203 9 (1-x)NaPO3 for x< 0.125 Al(6) was dominant, but at higher alumina contents Al(4) becomes favoured [245].…”
Section: Aluminophosphatesmentioning
confidence: 99%
“…30 The overlapping in the bands observed at 350°C and 430°C may be assigned to [AIOs] units having different binding angles. 30 It is interesting to note that the isotropic chemical shift is moved to the strong fields. This may be because of the presence of phosphorus, in particular, within the second sphere of coordination.…”
Section: %mentioning
confidence: 98%
“…Among them, Al 2 O 3 is a significant electro ceramic material with low values of dielectric loss and dielectric constant. Introducing Al 2 O 3 into the lithium phosphate glass system alters the cross-links between PO 4 tetrahedra in the sample and reported to occupy both AlO 4 tetrahedral sites and AlO 6 octahedral sites in the glass network that act as network formers and modifiers [8]. Selenium (Se) is disadvantaged because of its short lifetime and low sensitivity.…”
Section: Introductionmentioning
confidence: 99%